Migration and health, a look from the 2018 Census in Colombia - Martínez-Santa, Jaime (2021)
Introduction. The human being is characterized by having specific development spheres such as social, physical, family, spiritual and emotional.People known as migrants because they are outside their cultural, family and community sphere, and under atypical conditions they adopt new practices and styles of life, which causes risks to their own health and to the community by which they have been welcomed. Methodology. A descriptive study was carried out with the following variables from the 2018 Colombian census: five-year ages, sex, year of arrival in the country , any health problem in the last 30 days, main treatment of the health problem, attention to the health problem, quality of health service provision, any difficulty in their daily life, health insurance, barriers to access to services health, barriers to early childhood care services. Results. Health care for the migrant population in Colombia is not on the fringes of e the one that had its own population and there is no major difference in terms of quality and coverage, gender and access barriers, which are equal to the general population without differences with respect to the child population. Although health insurance is lower than the general population, only half of the migrants give formal treatment to their health problems. Conclusion. Specific policies should be established to promote health care for migrants, as this is a challenge for public health due to access policies and the care provided.